Persepsi Risiko dan Kesesuaian Syariah dalam Aktivitas Trading Forex Generasi Z: Analisis Pengaruh Konten Influencer - Yasir Basavey; Ashlihah; Bekti Widyaningsih (Lembaga Yasin AlSys, 2026)
Although forex trading, financial technology, and social media have been widely studied, research specifically integrating risk perception, Sharia compliance, and the influence of influencer content on Generation Z’s trading behavior remains limited. This study aims to analyze Generation Z’s understanding of forex trading risks, examine the role of influencer content in shaping their perceptions, and explore the relationships among influencer content consumption, risk perception, Sharia considerations, and trading decision-making. The study employed a qualitative approach with a descriptive case study design involving four Generation Z informants selected through purposive sampling. Data were collected through in-depth interviews and documentation and were subsequently analyzed using Miles and Huberman’s interactive analysis model. Data credibility was assessed through source and technique triangulation. The findings indicate that the informants’ understanding of risk developed through empirical experience encompassing financial, psychological, and Sharia dimensions. Influencer content shaped initially optimistic perceptions of forex trading, but its influence diminished as experience increased, leading the informants to become more critical in verifying information. Trading decisions were formed through the interaction among exposure to influencer content, risk perception, and considerations of Sharia compliance. These findings broaden the understanding of Generation Z’s financial behavior in the digital era and contribute to the development of Islamic Behavioral Finance studies. This study emphasizes the importance of financial literacy, critical thinking skills, and an understanding of Sharia principles in promoting more responsible trading decisions. The implications of this study are directed toward strengthening Islamic financial literacy by educational institutions, regulators, and digital content creators, as well as developing further research involving a broader range of informants and digital investment platforms.